A single-inductor thermoelectric and photovoltaic hybrid harvesting interface with time-multiplexed technology and accurate zero current detector. (July 2021) - Liu, Lianxi; Zhang, Peichao; Liao, Xufeng; Zhu, Zhangming
Abstract: This paper presents a single-inductor thermoelectric and photovoltaic hybrid harvesting interface. The time-multiplexed technology is proposed to harvest the dual-energy sources within one operating cycle, providing more load power in smaller system volume. Furthermore, the proposed accurate zero current detector can avoid advance or delay of the current detection in discontinuous conduction mode, thereby improving power conversion efficiency. The proposed interface was implemented in a 0.18 ​μm CMOS process with the area of 1.68 ​× ​1.31 ​mm 2 . The open-circuit-voltage range of the TE and PV transducers is from 0.1 ​V to 0.4 ​V and 0.2 ​V–1 ​V, respectively. The measured results show that the proposed interface harvests PV and TE energy synergistically in one operating cycle, and the TEH time and the PVH time account for about 48% and 4% respectively. The peak tracking efficiency of TEH and PVH are 98% and 98.1%, respectively. The peak power conversion efficiency reaches 85.7% when the output of TE is 300 ​mV and PV is 1 ​V.